Aplikasi Pengarsipan Surat Menggunakan PHP dan MySQL di Kecamatan Parungkuda Kabupaten Sukabumi - Ridwan; Wulan (LP2M CBI PRESS, 2020)
Parungkuda sub-district is part of the regional government area of Sukabumi Regency which is located at Jalan Raya Siliwangi No.58 Tel. (0266) 531002 Postal Code 43357. Established in 1940 with a land area of 2,701.00 Ha. As part of the mission to optimize public services, it is necessary to have an orderly and neat archive management so that the work process in the district of Parungkuda can be faster and improved in terms of services. For this reason, an information system is needed to manage the records. This application was created using PHP and MySQL. Keywords: Parungkuda, Arsip, PHP, MySQL